ISOLATION AND SELECTION OF ANTAGONISTIC BACTERIA TO RALSTONIA SOLANACEARUM CAUSED BACTERIAL WILT DISEASE ON GROUNDNUT AND SESAME - Kiều, Lê Như; Minh, Trần Quang; Thanh Thuỷ, Lê Thị; Huân, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYChemical pesticides are widely used to control diseases. However, the use of these pesticides can be expensive. They may also play a dominant role in environmental pollution, such as groundwater contamination. Thus, using biological control agents, especially biopesticieds, to fight such disease is gaining increasing momentum in the agricultural biotechnology research. This paper bring out the results of isolation and selection the antagonistic bacteria to make micro-product (biopesticieds) for controlling bacterial wilt disease on groudnut and sesame. 10 isolates of antagonistic bacteria to Ralstonia solanacearum have selected, which are not harmful to plant and mice. Among them CX5 belonging to Bacillus and PX1 is Pseudomonas. The both CX5 and PX1 can control bacterial wilt disease on groundnut, sesame and Plant-Growth-Promoting Rhizobacteria (PGPR). So these isolates are selected to control bacterial wilt disease on groudnut and sesame. When using CX5 strain reduced 66.64% of died sesame, 74.41% groudnud; PX1 reduced 71.31% of died sesame plant and 61.3% on groundnut, respectively.